Fabrication of liquid-infused textured surfaces (LITS): The effect of surface textures on anti-icing properties and durability. (August 2022) - Heydarian, Samaneh; Maghsoudi, Khosrow; Jafari, Reza; Gauthier, Hellene; Momen, Gelareh
Abstract: Icephobic surfaces offer an effective solution to protect the infrastructures subjected to harsh cold-weather environment and increase their efficiency. Inspired by the Nepenthes pitcher plant, liquid-infused coatings have received much interest as a potential cost-effective anti-icing solution. In this paper, we developed liquid-infused textured surfaces (LITS) through chemical etching followed by a replication method. We assessed the effect of viscosity (50 and 500 cSt) and the infusion percentages of lubricant on the morphology and icephobicity of the produced surfaces. Lubricant-infused silicone surfaces are normally obtained by combining a textured surface morphology and slipperiness. We therefore evaluated the wettability, morphology, and the localized surface elasticity maps of the fabricated surfaces using a goniometer, scanning electron microscopy (SEM), and atomic force microscopy (AFM), respectively. The icephobic performance of the samples was studied by differential scanning calorimetry (DSC), push-off tests, and freezing delay time measurements. Our observations of the anti-icing nature of the produced LITS confirmed that the heat insulation effect of the lubricant lowered the ice nucleation temperature considerably compared with non-oil surfaces. The prepared LITS presented an ice adhesion strength of less than 20 kPa, four orders of magnitude lower than that of a pristine surface. Surficial microtextures are critical for reducing the rate of oil depletion through the trapping of oil within the surface microstructures. Our designed lubricant-infused surfaces present more durable and stable anti-icing characteristics over the long term than smooth lubricant-infused surfaces. Graphical Abstract: ga1